Black Civil Rights in America - VERNEY, Kevern (Routledge, 2000)
This book is the authoritative introduction to the history of black civil rights in the USA. It provides a clear and useful guide to the political, social and cultural history of black Americans and their pursuit of equal rights and recognition from 1865 through to the present day.